Questions from the fourth son: A clinician reflects on immunomonitoring, surrogate markers and systems biology - Charles Wiseman; M.D. (Mathematical Biosciences and Engineering)
The fourth son is the one who doesn't even know how to ask a question. Tumor immunology is challenged by the failure to identify reliable surrogate markers in vaccine and other experimental therapies for cancer; perhaps investigators haven't yet asked the right questions. Unlike prophylactic vaccines for infectious disease, where the development of antibody is considered a satisfactory endpoint, no such endpoint exists for human therapeutic vaccines. Why is this? Despite an extensive roster of in vitro assays that correlate immune responses to favorable clinical outcomes, no assay is sufficiently reliable to be usefully predictive for vaccine therapy. The discussion reviews some of the historical developments in tumor immunology and the problem of defining a causal relationship when strong correlations are identified. The development of mathematical models from empirical data may help inform the clinician/scientist about underlying mechanisms and help frame new testable hypotheses.